Multitafsir Pasal 218 dan 219 KUHP dalam Tindak Pidana Penghinaan Presiden - Sinaga, Jusnizar; Esther, July; Nainggolan, Ojak (CV Rewang Rencang, 2025)
The enactment of Law Number 1 of 2023 reinstates the offense of insulting the President under Articles 218 and 219 of the Criminal Code. This study examines the differences in the normative construction of these provisions and their implications for legal certainty and freedom of expression. Employing normative legal research with statutory and conceptual approaches, the findings indicate that Article 218 emphasizes the substance of insult with a public interest exception, while Article 219 focuses on dissemination without clear limitations regarding intent. This ambiguity risks multiple interpretations and potential criminalization of criticism. Therefore, judicial interpretative guidelines are required to clarify intent and ensure proportional application.